A DFT-based analysis of adsorption performance of Zn2+ on vacancy defected carbon nanotubes. (1st February 2023) - Fan, Qingqing; An, Libao; Zhu, Zhiming
Abstract: In this paper, the adsorption performance of Zn 2+ on the vacancy defected carbon nanotube (V-CNT) was studied by using the first-principles calculation based on density functional theory. The results showed that, compared with the pristine carbon nanotube (P-CNT), the final adsorption distance between the V-CNT and Zn 2+ was considerably decreased, while the adsorption energy and charge transfer amount between them were greatly increased. These results, along with a computing on the charge density, all indicated that the adsorption of Zn 2+ on the V-CNT was chemisorption. Analysis on the partial density of states confirmed the formation of orbital hybridization between the V-CNT and Zn 2+ . In addition, the energy gap of the V-CNT was decreased significantly after the adsorption of Zn 2+ . Therefore, vacancy defected carbon nanotubes have a great application potential in the detection and adsorption of Zn 2+ ions in wastewater. Highlights: Vacancy defects can greatly improve the adsorption performance of CNTs with Zn 2+ . Stable chemisorption occurs between vacancy defected CNTs and Zn 2+ . Conductivity of vacancy defected CNTs changes evidently upon Zn 2+ adsorption. Vacancy defected CNTs would be a promising material for detecting Zn 2+ ions.